Creating Financial Infrastructure in a Large Transition Economy – Lessons from China’s New Credit Bureau - Paramanathan, Prashan; Huang, Lin (World Bank, Washington, DC, 2012)
International Financial Corporation (IFC) and the World Bank have in recent years promoted the implementation of credit bureaus as a way of improving access to finance for both individuals and businesses. In 2003, no such structure existed for consumer credit information in China. Not only was access to financing reduced, but the quality of the entire lending industry was also affected nonperforming loans represented a significant proportion of the portfolio, risk management practices were weak, and loans were poorly monitored. However, as this smart lesson describes, creating financial infrastructure such as a consumer credit bureau in large countries presents a unique set of challenges.